1997
DOI: 10.5694/j.1326-5377.1997.tb140072.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis of the knee in retired, elite Australian Rules footballers

Abstract: Objective: To determine the functional and radiological status of knee joints of retired Australian Rules footballers compared with those of active community members. Design: Retrospective cohort study. Participants: Fifty retired elite footballers aged 34–85 years (mean, 53.7 years; SD, 11.4) from four AFL clubs and 50 age‐matched controls (35–79 years; mean, 55.7 years; SD, 12.4) who had played no contact sport since their teenage years. Main outcome measures: Severity of knee functional osteoarthritis as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 9 publications
0
51
0
6
Order By: Relevance
“…6 These limitations may be associated with poorer outcomes from ACL reconstructions with reports of failure and recurrent instability in 10-15% of cases. [7][8][9][10] Tissue engineering strategies are being studied to address the limitations associated with current tendon graft technologies. Most current tissue engineering techniques being investigated involve the use of natural or synthetic polymer scaffolds to provide an integrating and degradable structure for cellular attachment.…”
Section: Introductionmentioning
confidence: 99%
“…6 These limitations may be associated with poorer outcomes from ACL reconstructions with reports of failure and recurrent instability in 10-15% of cases. [7][8][9][10] Tissue engineering strategies are being studied to address the limitations associated with current tendon graft technologies. Most current tissue engineering techniques being investigated involve the use of natural or synthetic polymer scaffolds to provide an integrating and degradable structure for cellular attachment.…”
Section: Introductionmentioning
confidence: 99%
“…Although relatively low, the majority of ACL ruptures occur in young athletes, with young female athletes at greater risk than their male counterparts 3 4. An ACL rupture is not only one of the most severe injuries sustained in sports,5 but also places the individual at up to 105 times greater risk of osteoarthritis 6. A significantly increased risk of ACL ruptures has been shown to be associated with regular participation in sport, particularly among sports requiring change in direction and rapid deceleration during cutting, pivoting and landing 7 8.…”
Section: Introductionmentioning
confidence: 99%
“…56 Non-statistically significant differences between athletes and controls were found in another 2 studies. 57,58 Of the remaining 6 studies, Deacon et al, 59 in the only study with a control group, reported that the study group (50 former elite football players) had a significantly greater prevalence and severity of functional and radiographically confirmed knee OA than the control group. The 5 remaining studies reported varying rates of knee OA (26%-63%).…”
Section: Evaluation Of the Development Of Knee Oamentioning
confidence: 97%